ANALISIS ADANYA PAY LATER DALAM MARKETPLACE TERHADAP DAYA BELI MASYARAKAT - Audrey Nathania Early Prasetya (LPPM Universitas Bina Bangsa, 2023)
The development of e-commerce in Indonesia has had an impact on payment methods that initially only used paper-based and card-based cash payments, but are now being introduced to new electronic-based payment systems. Pay Later is a type of electronic-based payment in the form of online credit. The use of Pay Later is estimated to be one of the triggers for the behavior of increasing purchasing power. The purpose of this study is to find out whether there is an increase in people's purchasing power with the emergence of the Pay Later payment system. This study uses a qualitative descriptive analysis method. The results of this study indicate that the use of e-commerce, especially in the Pay Later payment system, positively affects people's purchasing power. Which means that with the Pay Later feature, people's purchasing power is increasing